EFFECT OF FLOUR AND PAPAYA LEAF EXTRACT (CaricapapayaL) IN FEED TO AMMONIA CONCENTRATION, VOLATILE FATTY ACIDS AND MICROBIAL PROTEIN SYNTHESIS IN VITRO - Pipin Sairullah; Siti Chuzaemi; Herni Sudarwati (TERNAK TROPIKA Journal of Tropical Animal Production, 2016)
This research was conducted to investigate the effect of flour and papaya leaf extract (Carica papaya L) on a mixed diet of napier grass (Pennisetum purpureum Schaum) and pollard (Triticumaestivum) to the concentration ammonia, Volatile Fatty Acids (VFA’s) and microbial protein synthesis invitro. This research method was an experiment in laboratory with Randomized Block Design (RBD) using 5 treatments with 3 replications. the treatment were P0 : Control Ration (napier grass + pollard ratio of 1:1 in the DM), P1 : P0 + 2.0% papaya leaf flour DM, P2 : P0 + 4.0% papaya leaf flour DM, P3 : P0 + extract DM 2.0% papaya leaves, P4 : P0 + extract DM 4.0 % papaya leaves. The measured variables were concentration of ammonia incubating rumen fluid 24 hour, concentration of VFA’s and microbial protein synthesis in the rumen fluid incubation 48 hour. Data were analyzed using variance (ANOVA), if there any differences in treatment, then continued with Duncan Multiple Range Test (DMRT). The results of research that provides highly significant difference (P <0.01) the concentration of ammonia and microbial protein synthesis, but not significantly (P> 0.05) against the VFA’s. Conclusion of the research was the additional flour and papaya leaf extract on blanding of napier grass and pollard can increase the concentration of ammonia, VFA’s, and microbial protein synthesis. The best treatment is the addition of papaya leaf flour 4.0 % (P2) because it can increase the concentration of ammonia and microbial protein synthesis, treatment with the addition of papaya leaf extract 2.0% (P3) can disposed increase the VFA’s. The suggestion of this research is that papaya leaf flour 4,0 % (P2) could be added on the woof because it can improve ammonia concentration and synthesis protein of microbe, also this is need to do a deep research to know what the effect of additional of flour and papaya leaf extract on protozoa population based on in vitro. Keywords : Papaya leaf, ammonia, Volatile Fatty Acids, in vitro.